The Protonation-Deprotonation Kinetics of the Protonated Schiff Base in Bicelle Bacteriorhodopsin Crystals - Sanii, Laurie S. (Biophysical Society, 2005)
In the recently published x-ray crystal structure of the “bicelle” bacteriorhodopsin (bbR) crystal, the protein has quite a different structure from the native and the in cubo bacteriorhodopsin (cbR) crystal. Instead of packing in parallel trimers as do the native membrane and the cbR crystals, in the bbR crystal the protein packs as antiparallel monomers. To date, no functional studies have been performed, to our knowledge, to investigate if the photocycle is observed in this novel protein packing structure. In this study, both Raman and time-resolved transient absorption spectroscopy are used to both confirm the presence of the photocycle and investigate the deprotonation-reprotonation kinetics of the Schiff base proton in the bbR crystal. The observed rates of deprotonation and reprotonation processes of its Schiff base have been compared to those observed for native bR under the same conditions. Unlike the previously observed similarity of the rates of these processes for cbR crystals and those for native bacteriorhodopsin (bR), in bbR crystals the rate of deprotonation has increased by 300%, and the rate of reprotonation has decreased by nearly 700%. These results are discussed in light of the changes observed when native bR is delipidated or monomerized by detergents. Both the change of the hydrophobicity of the environment around the protonated Schiff base and Asp(85) and Asp(96) (which could change the pK(a) values of proton donor-acceptor pairs) and the water structure in the bbR crystal are offered as possible explanations for the different observations.